Pengaruh Persepsi Harga dan Kualitas Produk terhadap Keputusan Pembelian Emina Bright Stuff : Survei pada Konsumen Emina Bright Stuff di Tasikmalaya - Elsi Nopita Sari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This Study aims to determine the effect of perceived price and product quality on purchasing decisions on the Emina Bright Stuff method. The research used in this study is a quantitative methode with a research sample of 100 respondents from consumers of Emina Bright Stuff. The data used is primary data. The analytical tool used is Multiple Linier Regressions Analysis using SPSS v.25Software. The Result showed that the price perception of Emina Bright Stuff consumers had very good criteria. Product quality at Emina Bright Stuff has very good criteria. Simultaneously, the perception of price and product quality has a significant influence on purchasing decision. Partially , price perception has a significant effect on purchasing decisions. Partially, product quality has a significant effect on purchasing decisions.